Alocação de modem PLC utilizando SNR em uma rede elétrica de baixa tensão - Padua, Fabiano João Leoncio de [UNESP] (2014)
This thesis presents a mathematical model of mixed integer linear programming (MILP) to the optimal allocation problem of PLC modems in a low voltage electrical network distribution. Modem PLC can provide to the subscribers the access to external data using the existing infrastructure of low-voltage grid. Using a MILP model ensures the optimum convergence using existing optimization software. The proposed model considers as the main constraint of operation the signal noise ratio (SNR) between modems PLC. Matrix SNR is generated through a model of transmission line based on circuit of two ports (Quadrupole). The results presented using an unreal system with 7 poles and three real systems with 13, 17 and 24 poles to test the efficiency and precision of the proposed methodology